PENGARUH PENGHINDARAN PAJAK, KEPEMILIKAN INSTITUSIONAL DAN PROFITABILITAS TERHADAP BIAYA HUTANG - Sherly, Elvis Nopriyanti; Indriani, Rini; Suranta, Eddy (UNIB Press, 2016)
The purpose of this study is to prove the effect of tax avoidance, institutional ownership, and profitability on cost of debt.The sample consisted of 71 manufactured firms in listed in Indonesian Stock Exchange from 2011-2015 by using a purposive sampling method.The results of the study showed that the tax avoidance had negative effect on cost of debt. The meaning is getting smaller Cash Effective Tax Rate the cost of debt incurred greater. The results of this study also showed that the institutional ownership doesn’t had effect on cost of debt. Furthermore, the result of Return on Assets (ROA) as proxy profitability had a negative effect on cost of debt. The meaning that the higher the profitability of the company then the company will have a high internal funds that can be used in making the use of debt financing is getting smaller which causes the cost of debt also becomes smaller.